Bamboo—Phyllostachys spp. - James M. Stephens (EDIS)
This document discusses the cultivation and uses of bamboo (Phyllostachys spp.), highlighting its value as a vegetable. The article describes bamboo's perennial nature, propagation methods, and the process of preparing bamboo shoots for cooking. It emphasizes the importance of proper planting techniques and the culinary versatility of bamboo sprouts, which can be used in various dishes or eaten raw in salads. Original publication date April 1994.